Association between polygenic risk score and risk of myopia - Ghorbani Mojarrad, N; Plotnikov, D; Williams, C; Guggenheim, JA (American Medical Association, 2019)
Importance Myopia is a leading cause of untreatable visual impairment and is increasing in prevalence worldwide. Interventions for slowing childhood myopia progression have shown success in randomized clinical trials; hence, there is a need to identify which children would benefit most from treatment intervention.